LINGUISTIC LANDSCAPE IN THE COMMERCIAL DISTRICT OF SURYA KENCANA, BOGOR - Kanya Aimee Saltiga Putri; Rindu Rindang Cintakami; Maliq Rizqy Attaya; Dewi Yanti (Linguists : Journal of Linguistics and Language Teaching, 2026)
This study explores the linguistic landscape of Surya Kencana Street in Bogor City, Indonesia, a historically rich and culturally diverse area. Surya Kencana is characterized by multilingual dynamics, making it an ideal location to investigate how language functions in urban spaces. Through photographic documentation, a total of 74 photographs capture various public signs within the area, showcasing how language is represented in this urban landscape. The research categorizes public signage into three types based on language use: monolingual, bilingual, and multilingual. The primary objective of this research is to understand the dynamics of language use in Surya Kencana, particularly the roles of Indonesian, English, and Sundanese in public signage. The study also aims to investigate the influence of globalization and local language policies on the linguistic landscape, focusing on the commodification of language in a historical commercial district. This research fills a gap in existing studies by addressing the limited research on linguistic landscapes in secondary Indonesian cities, and specifically by examining the absence of studies focusing on language commodification in local commercial districts. It also explores the discrepancies between national language policies and the actual language practices visible in public signage. The findings reveal that Indonesian, as the official national language, dominates the signage throughout the area, while English is widely used for its commercial and international significance. Interestingly, the use of Sundanese is relatively minimal, especially in economic and business contexts. This suggests that Indonesian and English hold symbolic and commercial value, with Sundanese being marginalized in the public sphere. Moreover, the linguistic landscape of Surya Kencana continues to evolve, reflecting a new identity shaped by processes of language commodification. This research contributes to the growing body of literature on linguistic landscapes in Indonesia, offering insights into the role of language in the construction of urban identities and power relations. Furthermore, it highlights the complex interplay between language policy, market forces, and social dynamics in shaping the linguistic environment of a commercial area.